Hubungan antara Stress Akademik dengan Fatigue pada Mahasiswa Universitas Negeri Padang - Ramadhani, Nurul Fajriati; Utami, Rahayu Hardianti (Lembaga Yasin AlSys, 2024)
Fatigue is a subjective state of exhaustion associated with reduced motivation, activity, prolonged mental, or boredom that occurs in situations. Academic stress is a form of stress that occurs due to stressors in the teaching and learning process or things related to learning activities. This study aims to determine the relationship between academic stress and fatigue in students. This study uses quantitative methods with Pearson product moment analysis. The population of this research is Padang State University students from 2021 to 2023. The sampling technique for this study used stratified random sampling with a total sample of 468 people. This research instrument uses the Perceived Sources of Academic Stress scale and the Multidimensional Fatigue Inventory-Short From. Based on the results of the data obtained the value of r = 0.593 with p = 0.000 (sig. <0.05). So it can be said that there is a positive relationship between academic stress and fatigue in Padang State University students from 2021 to 2023. The results show that the high academic stress felt by students is followed by an increase in fatigue felt by students. So it is expected to improve the overall well-being of students and support in achieving optimal academic results without excessive pressure.